Social Networks that Made a Revolution in Recruitment; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Krinitsyna Z. V. Zoya Vasilievna (2016, 2016)
Title screen